Reverse Commerce (Re-Commerce) Design for the Sale of Secondhand Eco print Products as an Implementation of Circular Economy in Indonesia - Rilis Akista Tria Sasti; Didiet Widiatmoko Soewardikoen; Wirania Swasty (Jurnal Indonesia Sosial Teknologi, 2025)
The fashion industry contributes greatly to environmental pollution due to high production waste. One solution to reduce this impact is through the concept of a circular economy by encouraging sustainable consumption behavior, including re-commerce or reselling used goods. This study aims to design a re-commerce platform for used ecoprint products as an implementation of a circular economy in Indonesia. The methods used are the Double Diamond and Empathy Map approaches to understand user needs and design a wireframe-based UI/UX prototype. The results of the study indicate that there is great potential in the development of ecoprint re-commerce in Indonesia, supported by consumer awareness of environmentally friendly products. The designed platform, "Selaras", offers main features such as buying and selling used ecoprint products, online garage sales, and upcycling boutiques. In conclusion, this re-commerce design can be an innovative solution in extending the life cycle of fashion products and encouraging sustainable consumption behavior in Indonesia.